Hormonome Dynamics During Microgametogenesis in Different Nicotiana Species - Záveská Drábková, Lenka; Pokorná, Eva; Dobrev, Petre I.; Kůrková, Jana; Steinbachová, Lenka; Honys, David; Motyka, Václav (Frontiers in Plant Science, 2021)
Plant microgametogenesis involves stages leading to the progressive development of unicellular microspores into mature pollen. Despite the active and continuing interest in the study of male reproductive development, little is still known about the hormonomics at each ontogenetic stage. In this work, we characterized the profiles and dynamics of phytohormones during the process of microgametogenesis in four Nicotiana species (Nicotiana tabacum, Nicotiana alata, Nicotiana langsdorffii, and Nicotiana mutabilis). Taking advantage of advanced HPLC-ESI-MS/MS, twenty to thirty endogenous hormone derivatives were identified throughout pollen ontogenesis, including cytokinins, auxins, ABA and its derivatives, jasmonates, and phenolic compounds. The spectra of endogenous phytohormones changed dynamically during tobacco pollen ontogeny, indicating their important role in pollen growth and development. The different dynamics in the accumulation of endogenous phytohormones during pollen ontogenesis between N. tabacum (section Nicotiana) and the other three species (section Alatae) reflects their different phylogenetic positions and origin within the genus Nicotiana. We demonstrated the involvement of certain phytohormone forms, such as cis-zeatin- and methylthiol-type CKs, some derivatives of abscisic acid, phenylacetic and benzoic acids, in pollen development for the first time here. Our results suggest that unequal levels of endogenous hormones and the presence of specific derivatives may be characteristic for pollen development in different phylogenetic plant groups. These results represent the currently most comprehensive study of plant hormones during the process of pollen development.